2021
DOI: 10.3390/antibiotics10050582
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Amoxicillin-Clavulanate Resistance in Community-Onset Urinary Tract Infections Caused by Escherichia coli or Klebsiella pneumoniae: The Role of Prior Exposure to Fluoroquinolones

Abstract: Background: High rates of amoxicillin-clavulanate (AMC) resistance among Enterobacterales isolated from urinary tract infections (UTIs) were observed in our area. The aim of this study was to identify risk factors associated with AMC resistance in patients with community-onset UTI in emergency departments (EDs). Methods: A retrospective study was performed of all ED patients with positive urine cultures for Escherichia coli or Klebsiella pneumoniae in a Spanish tertiary-care hospital. Results: 330 urine cultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…This agent is considered an adequate empiric treatment for UTIs in specific patient groups like children, elderly patients, or during pregnancy. Similar to our results were reported by Martínez-Casanova and Gaspari (7,8).…”
Section: Discussionsupporting
confidence: 93%
“…This agent is considered an adequate empiric treatment for UTIs in specific patient groups like children, elderly patients, or during pregnancy. Similar to our results were reported by Martínez-Casanova and Gaspari (7,8).…”
Section: Discussionsupporting
confidence: 93%
“…Amoxicillin/clavulanic acid is among the ABs commonly used to treat uncomplicated UTI. In this study, we found a high level of resistance (37.3%-47.1%) to amoxicillin/clavulanic acid in Enterobacterales, which could endanger its future empirical use for treatment of UTIs [36] as happened with amoxicillin alone, whose use in uncomplicated UTI is no longer recommended [29].…”
Section: Discussionmentioning
confidence: 99%
“…Clavulanic acid is a -lactamase inhibitor that can protect amoxicillin from betalactamase hydrolysis reactions (Pratiwi, 2017). However, a study reported that Escherichia coli and Klebsiella pneumoniae were resistant to Amoxicillin-clavulanate (Martínez-Casanova et al, 2021). Drug Utilization (DU 90%) can be interpreted as a list of drugs that are included in the accumulation of 90% of drug use in a location.…”
Section: Quantitative Analysis Of Antibiotic Usementioning
confidence: 99%